(untitled) (World Economics and Finance Bulletin, 2023)
The article analyzes and compares the concept of the digital economy and identifies problems in its application. The process of using the totality of economic resources in the national economy in the digital economy is considered from the point of view of digital technologies. A methodology for quantitative and information analysis and a mechanism for its operation in assessing digitalization has been developed, and it has also been proposed to use the concept of an economic functionality index in the digitalization of information resources.